The use of virtual reality in a psychiatric intensive care unit: a pilot study. (1st September 2021) - Mark, Isabel; Bell, Darren; Kirsh, Leiah; O'Brien, Aileen
With online options becoming increasingly popular within healthcare, virtual reality (VR) is a rapidly emerging field. This study assessed the feasibility and tolerability of using a VR headset in a psychiatric intensive care unit (PICU). Inpatients were invited to watch VR videos under supervision. 25 patients were considered, with 21 meeting the inclusion criteria and 17 taking part. All 17 participants were able to tolerate the VR and all reported it as a positive experience; 16 (94.1%) stated they would like to repeat the process; 3 (17.6%) reported an adverse effect and 2 (11.8%) reported an aspect which was not liked; We demonstrate that VR can be used and tolerated within the high-stress environment of a PICU. Further investigation is now needed to assess potential therapeutic benefits for agitation and psychotic symptoms in PICU.